Smoked - Mancusi, Mari (Scorched, 2015)
"When Team Dragon finally rescues Emmy--now a full-grown dragon--they think the future is safe. Until Emmy reveals a secret: she's laid two dragon eggs, and her offspring may bring about the fiery apocalypse they've all fought so hard to prevent"--Provided by publisher.